Diagnostic value of GPX4, IL-13, periostin, and thiol/disulfide balance in adult patients with scorpion envenomation: a prospective observational study - Buyukaslan, Hasan; Koçakoğlu, Şenay (Frontiers in Toxicology, 2025)
Background and ObjectivesScorpion envenomation presents with a wide spectrum of clinical manifestations, ranging from mild local symptoms to severe systemic complications. This study aimed to evaluate the diagnostic and prognostic utility of GPX4, IL-13, periostin, SDF-4, and thiol/disulfide homeostasis parameters in adult patients with confirmed scorpion envenomation.Materials and MethodsThis prospective observational study included 60 adult patients with confirmed scorpion stings and 33 healthy controls. Serum levels of GPX4, IL-13, periostin, and SDF-4 were measured using ELISA. Thiol/disulfide balance was evaluated by spectrophotometric assay. Clinical severity was graded using a four-level scale (Grade I–IV) based on local and systemic findings. Receiver operating characteristic (ROC) analysis and logistic regression were performed to assess the diagnostic performance and independent predictive value of biomarkers.ResultsPatients exhibited significantly lower GPX4, native thiol, and total thiol levels, and higher disulfide, IL-13, periostin, and SDF-4 levels compared to controls (p < 0.001). The disulfide/native thiol and disulfide/total thiol ratios were also elevated. GPX4 (AUC = 0.984), SDF-4 (AUC = 0.900), and periostin (AUC = 0.850) demonstrated excellent diagnostic accuracy. GPX4 and disulfide levels were identified as independent predictors of envenomation. Biomarker levels significantly correlated with clinical severity grades.ConclusionOxidative and inflammatory biomarkers, particularly GPX4, disulfide/native thiol ratio, IL-13, and periostin, provide diagnostic and prognostic value in scorpion envenomation. Incorporating these parameters into clinical assessment may enhance early risk stratification and guide management in the emergency setting.